Driving Mechanisms of Sedimentary 230Th and 231Pa Variability in the Western Arctic Ocean Through the Last Glacial Cycle. Issue 7 (30th June 2021) - Xu, Qian; Xiao, Wenshen; Wang, Rujian; Süfke, Finn; Lippold, Jörg; Not, Christelle
Abstract: Concentration profiles of excess 230 Th and 231 Pa ( 230 Thxs and 231 Paxs ) in Arctic Ocean sediment cores exhibit strong temporal variabilities, but the mechanisms responsible for the variabilities remain poorly understood. Here, we present new 230 Thxs and 231 Paxs profiles from the Mendeleev Ridge to examine downcore 230 Thxs and 231 Paxs distributions and their connection to environmental conditions in the Arctic. Measurable concentrations of 230 Thxs ( 231 Paxs ) from the new record display an alternation of " 230 Thxs ( 231 Paxs )‐rich" and " 230 Thxs ( 231 Paxs )‐poor" sections as observed in the other cores from the Mendeleev Ridge. Sedimentary characteristics reveal that this alternation does not directly correspond to interglacial‐glacial cycles. The 230 Thxs and 231 Paxs concentrations show an inverse relationship to their corresponding sedimentation rates, suggesting the distributions of 230 Thxs and 231 Paxs are affected by variable dilution with terrigenous material. However, changes in lateral transport of these isotopes may also account for the observed oscillations. Sedimentary cumulative inventories of 230 Thxs show evidence for a net deficit of 230 Th in the sediments during the last glacial period, possibly due to a lack of scavenging material in general. Key Points: Local conditions influencing 230 Thxs and 231 Paxs burial were superimposed by glacial/interglacial changes in the sedimentary environment Imbalance between Arctic sedimentary 230 Thxs and 231 Paxs and water column production existed during the last glacial period Sediment focusing has occurred in the western Arctic due to meltwater discharge events